Tailored job coaching for people with severe mental illness living in supported housing settings: A realist approach - Joep Binkhorst; Josje Dikkers; Roland Blonk; Marc van Veldhoven (PLoS ONE, 2026)
Background For people with severe mental illness (SMI) residing in supported housing settings, finding and maintaining paid or unpaid work is challenging. This study was initiated to examine how professionals tailor job coaching trajectories to effectively address the specific needs of clients. The aim was to unravel the complexity of these trajectories, providing a deeper understanding of how and under what circumstances people with SMI in supported housing can obtain and sustain meaningful daily activities, including paid or unpaid work, as part of their recovery journey. Methods Interviews were conducted with 24 clients with severe mental illness (SMI) and their job coaches (N = 15) in dyads. Additionally, two mixed focus group discussions were held with job coaches (n = 16) and their supervisors (n = 2). A realist evaluation approach was used to determine what works for whom, how, and under which conditions. Self-Determination Theory (SDT) served as the analytical framework to explore the motivational factors that drive clients to seek and retain paid or unpaid work. Results Our findings are structured in three sections, each focusing on context-intervention-mechanism-outcome (CIMO) configurations. These configurations illustrate how job coaches address clients’ needs for relatedness, competence and autonomy. The findings provide a deeper understanding of the inner workings of job coaching trajectories, showing how job coaches foster autonomous motivation and thereby enable clients to obtain and retain both paid and unpaid work. Conclusions This study highlights that there is no universal approach to job coaching. Job coaching requires a tailored approach with a strong emphasis on building personal-professional relationships and adapting interventions to individual circumstances.